The Little red hen Jerry Smath. - Smath, Jerry (Reading, Mass. Addison-Wesley, 1989)
When the Little Red Hen asks the other barnyard animals who will help with the planting, reaping, and other chores they all say, "Not I," but when the work is done they all want a reward.
Keywords: Folklore; Animals -- Folklore